2015
DOI: 10.1039/c5ra04077a
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Ti alloy with hydrophilicity, antibacterial activity and cytocompatibility

Abstract: Titanium-6 aluminium-4 vanadium (Ti64) alloy was modified to a hydrophilic, cytocompatible, antibacterial and bioactive surface via a simple cost effective chemical treatment method. A fine porous network structure of sodium hydrogen titanate (SHT) was formed on the Ti64 alloy surface by using sodium hydroxide treatment. The incorporated Na + ions are replaced by Ag + ions by a subsequent silver nitrate treatment. Contact angle measurement indicated that the silver containing Ti64 alloy surface is hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 67 publications
(133 reference statements)
1
20
0
Order By: Relevance
“…After the chemical reaction between activated carboxylic acid and chitosan, the broad peak ranging from 3750 to 2500 cm −1 , which confirmed the presence of carboxylic acid groups on the PU film, was removed from the obtained ATR‐FTIR spectrum. In addition, the peak appeared at 3320 cm −1 refers to the NH and OH groups on the chitosan chain . The characteristic peak at 1685 cm −1 confirms the formation of the amide group, resulting from the reaction of PAA with chitosan .…”
Section: Resultsmentioning
confidence: 90%
“…After the chemical reaction between activated carboxylic acid and chitosan, the broad peak ranging from 3750 to 2500 cm −1 , which confirmed the presence of carboxylic acid groups on the PU film, was removed from the obtained ATR‐FTIR spectrum. In addition, the peak appeared at 3320 cm −1 refers to the NH and OH groups on the chitosan chain . The characteristic peak at 1685 cm −1 confirms the formation of the amide group, resulting from the reaction of PAA with chitosan .…”
Section: Resultsmentioning
confidence: 90%
“…Kizuki et al [28] and Prabu et al [44] demonstrated that Ag can be induced into SHT formed on Ti and Ti-6Al-4V alloy as ion form by soaking the metals in 0.01-100 mM Ag(NO) 3 solution after the NaOH solution. However, metallic Ag particles were formed again when the treated metals were subsequently heat-treated at 600 • C [28].…”
Section: Discussionmentioning
confidence: 99%
“…[86][87][88][89][90] The peaks in both diffractograms were indexed to the alfa Ti phase, and no clear presence of the beta-Ti phase, and none of Ti oxides or other corrosion products was found, although ATR-FTIR results suggest the formation of Ti-O-Ti bond that could arise from surface TiO 2 . [91][92][93][94][95] The relatively higher peak intensities in the spectrum of epoxy reference coating arises from its lower thickness (ca. 10 micrometers) compared to that of the GO + Nd (ca.…”
Section: Surface Studies Of the Coated Ti6al4v Alloysmentioning
confidence: 99%